Evaluating educational reforms : Scandinavian perspectives - Haug, Peder, 1947-; Schwandt, Thomas A. (Emerald Publishing Limited : Information Age Publishing, 2003)
A Scandinavian perspective on evaluating educational reforms. The essays include: The Research Council of Norway Evaluating Reform 97; Models of Evaluation; and What's Being Done in the Name of Evaluation? Experiences Drawn from the Recent Evaluation of Schooling Reforms in Switzerland.
Papers presented at a seminar held at Oslo in October 2001.
Keywords: Educational evaluation -- Scandinavia -- Cross-cultural studies -- Congresses.; Educational evaluation -- Norway -- Congresses.; Educational change -- Scandinavia -- Evaluation -- Cross-cultural studies -- Congresses.; Action research in education -- Scandinavia -- Cross-cultural studies -- Congresses.; elektronické knihy; Conference papers and proceedings.; Education -- Educational Policy & Reform -- General.; Educational strategies and policy.; electronic books